Environmental discourse in Brazilian English-as-a-foreign-language textbooks: socio-discursive practices and their implications for developing students' critical environmental literacy. Issue 1 (31st January 2022) - Cristovão, Vera Lúcia Lopes; Sanches, Bruno; Smart, Graham
Abstract: This article reports on a study that investigated the extent to which the discourse used to approach environmental issues in English-as-a-Foreign-Language (EFL) textbooks in Brazilian public secondary schools helps students develop critical environmental literacy. We focused our discourse analysis on the outside materials incorporated into the content of the textbooks. To inform our discourse analysis, we drew on theories of discourse genres, discursive affordances and entextualisation. The primary conclusion we take from the study is that Brazilian textbook designers integrate outside materials to enhance the content of textbooks, and while this is a commendable aim, these outside materials are unsuitable for helping students develop critical environmental literacy. Although the textbooks may potentially succeed in cultivating a 'shallow' form of environmentalism that raises students' eco-awareness, they appear to fall short of providing an educational experience that would be appropriate for fostering students' criitical envir onmental literacy, and thereby preparing and motivating them to act in their daily lives in ways that further environmental sustainability.